Komponen bioaktif ekstrak akuades kayu manis (Cinnamomum burmanii Blume) asal Sumatra, Indonesia [Bioactive components of cinnamon aquades extract (Cinnamomum burmanii Blume) from Sumatra, Indonesia] - Verdini, Liana; Setiawan, Budi; Sinaga, Tiurma; Sulaeman, Ahmad; Wibawan, I Wayan Teguh (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Cinnamon is a type of plant that contains bioactive components and useful as a functional food used in the prevention of diabetes mellitus. The aim of this study was to identify the content of bioactive components of aquadest extract of cinnamon (Cinnamomum burmanii B.) using GC-MS. The results of the GC-MS analysis showed that there were eight different compounds contained in the aquadest cinnamon extract, namely cinnamaldehyde, coumarin, ethalic acid, phthalazinone, acetyl monoglyceride, itaconic anhydride, 3,5-dihydroxy-2-methyl-5,6-, and bis (2-ethylhexyl) platelets. The bioactive component of cinnamon identified in the Aceh region is coumarin at 37.01%. The bioactive component of cinnamon identified in the Jambi region was cinnamaldehyde of 33.50%. The bioactive component of cinnamon identified in West Sumatra is cinnamaldehyde of 17.49%. This study shows that there are different bioactive components from Sumatra, Indonesia. Chromatographic analysis using GC-MS showed that cinnamon from Sumatra, Indonesia contains bioactive components that have antihyperglycemic effects.Keywords: aquades extract, cinnamon, GC-MS, phytochemical